Extraterritoriality in Comparative Perspective - Buxbaum, Hannah L., (International Law E-Books Online, Collection 2025., 2025)
Extraterritoriality is often understood as an exceptional, sometimes even illegitimate, form of state lawmaking-yet it is pervasive in contemporary practice. Countries around the world rely on extraterritorial regulation to protect local markets, in areas including competition law and data privacy. It is also recognized as a useful strategy to promote international human rights, and to address shared challenges as diverse as transnational crime, tax base erosion, and climate change. The normalization of extraterritoriality as a legal technique, however, has by no means resolved longstanding debates about its place in the international legal order. Containing in-depth studies of fifteen legal systems, this volume provides a critical comparative perspective on those debates.